Corifollitropin Alfa Compared to Daily Recombinant FSH in in Vitro Fertilization Programmes: A Meta-Analysis of Randomized-Controlled Trials - Maria Cristina Budani; Stefania Fensore; Marco Di Marzio; Gian Mario Tiboni (IMR Press, 2023)
Background: Corifollitropin alfa (CFA) is a long-acting recombinant follicle-stimulating hormone (rFSH) used for controlled ovarian stimulation (COS). Several studies analyzing the clinical efficacy and safety of CFA compared to daily rFSH during COS have been carried out. The present study offers a meta-analysis of the randomized controlled trials (RCTs) on this topic. Methods: A computerized search of the published literature was carried out using PubMed, MEDLINE, Science direct and Google Scholar databases. The comparison between CFA and daily rFSH treatments during COS were investigated only in RCTs. The primary endpoint of the study is represented by the number of total oocytes retrieved at ovum pick-up. The studies included in the analysis were pooled together in order to estimate the log odds ratio (OR) or the mean difference (MD) along with the corresponding 95% confidence intervals (CI) by using a random effects model. The heterogeneity between the studies was evaluated with the Higgins and Chi-square tests. Results: The study examined a total of twelve RCTs published from 2004 to date and included a total of 4980 patients, with 2664 receiving CFA and 2316 patients receiving daily rFSH for COS. Women treated with CFA had higher number of total oocytes retrieved at ovum pick-up (MD 0.91, 95% CI [0.34, 1.49], p = 0.001), and higher number of metaphase II (MII) oocytes (MD 1.00, 95% CI [0.37, 1.62], p = 0.002) compared to those receiving daily rFSH. There were no significant differences between the two study groups regarding the other outcomes analyzed. The subgroup analysis performed comparing "normal" versus "poor" responders revealed that normal responders receiving CFA showed an higher cancellation rate, with respect to those receiving rFSH. Conclusions: This study shows that COS with CFA results in a higher number of oocytes retrieved at ovum pick-up in comparison with daily rFSH.